Effect of addendum parameters to the formability of aluminum AL 6303 - , Afzeri; M. S., Shahdan; Hussain Shah, Qasim (Trans Tech Publications, Switzerland, 2011)
Procedure of die design is mostly based on iterative try and error to obtain final design with good stamping formability. The stamping formability of sheet metal part is possible to be improved by adding addendum features at die model. In this paper discusses the effect of drawbars toward the formability of stamping process of aluminum AL6063. Effect of addendum size is evaluated Finite Element Simulation to prevent wrinkling and tearing. Simulation model is constructed by designing a simple die, punch and binder using variety drawbar diameters. The model further evaluated using LS-Dyna software interfaced by forming tool of LS-Prepost. Formability of the model is evaluated through yield stress, major strain and minor strain data. From the result of evaluation obtained that without draw beat, major/minor strain is above FLD while the formability is improved by applying 5 mm draw bead diameter.